The vegan matrix : understanding and discussing privilege among vegans to build a more inclusive and empowered movement - Joy, Melanie (Lantern Publishing & Media, 2020)
"In The Vegan Matrix, psychologist, longtime vegan advocate, and organizational head Dr. Melanie Joy explores a serious problem in the vegan movement: unexamined privilege. She also examines the struggle to talk effectively about this problem in a way that helps offset it. Using simple, straightforward language and a compassionate tone, Joy explains what privilege is, why it's so important for vegans to become aware of it, and how to talk about it in a way that deepens understanding and helps transform it. In so doing, Joy unpacks some of the many privileges that must be acknowledged and addressed, and calls for more inclusivity and diversity within vegan organizations and the movement as a whole. The Vegan Matrix is a call to awareness and action, empowering vegans to reach a broader audience and to help create a more compassionate and just world"--